Pengaruh Kualitas Produk, dan Citra Merek, Terhadap Keputusan Pembelian Konsumen Melalui Ekuitas Merek Pada Produk Kecantikan Somethinc - Alvina Hannah Ahmad; Desy Prastyani (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
As time progresses, people's lifestyles are starting to change because they are influenced by trends that occur in society, one of which is the increasing need for skincare by women and men. One of them is local products, presenting unique innovations and high quality, showing pride in local beauty in each product. This attraction has succeeded in winning the hearts of many people because of the superior quality ingredients and affordable prices for every product they provide. The method used in this research is quantitative data analysis with the technique used, namely purposive sampling. The sample for this research is working women aged minimum 17 years who have used some type of beauty product and are in the Jabodetabek area. Questionnaires were collected from 174 respondents, the data was then processed using the Structural Equation Model (SEM) method with Partial Least Square (PLS) version 4 technical application program tools. Based on the results of the analysis, it is known that the product quality influence variable has a positive influence on purchasing decisions. The results also found that the influence of product quality had a positive influence on brand equity, and there was a positive influence of brand image on purchasing decisions, and it was also found that brand image had a positive influence on brand equity. The final finding is that the brand equity variable with purchasing decisions does not have a positive influence. The implications of these findings provide insight for the growth of Somethinc skincare involving collaboration with influencers, improved product design, transparency of ingredient information, and promotional offers. This action is expected to improve brand image, product attractiveness and customer trust, supporting growth and a strong market position.